The Attacker's Advantage - Charan, Ram (HighBridge, 2015)
When Ram Charan (and Larry Bossidy) published Execution (over 2 million copies sold), they saw it as the playbook for both senior and middle managers in "the new game." But now, the game has changed. Business leaders find themselves operating in an era of persistent uncertainty moving at an unprecedented rate of change. Now the man Forbes magazine called "alone at the top of his profession . . . a guru, a corporate sage" returns with a new message for this challenging time.In The Attacker's Advantage, Charan reveals the upside of uncertainty for those leaders who are nimbly positioned to anticipate the catalysts of disruption and embrace change. He updates and adapts the principles of his previous bestsellers to address the current turbulent business environment, cutting through the veil of complexity to concentrate on the new customer needs and expectations and providing the tools for corporate leaders to take their companies to a higher level."He has the rare ability to distill meaningful from meaningless and transfer it to others in a quiet, effective way." -Jack Welch, former Chairman of GE"He knows more about corporate America than anyone." -Richard Harrington, CEO Thomson Reuters.